Acute Pericarditis Manifesting as Persistent Chest Pain Following Primary Percutaneous Coronary Intervention: A Missed Diagnosis - Vivek Mohanty; Sourabh Goswami; Rahul Choudhary (Heart Views)
Percutaneous coronary intervention (PCI) is a very rare cause of acute pericarditis. It usually develops after a latent period but can present early in case of procedural complications. A high degree of suspicion is required for diagnosis as most cases can be easily missed. Here, we highlight a case of 54-year-old admitted as a case of non-ST elevated myocardial infarction who in view of ongoing chest pain underwent urgent coronary angiography, followed by the primary PCI to left anterior descending artery after which the patient became pain-free. However, 12 h after the procedure, the patient developed severe persistent chest pain with positional and respiratory variation. He was suspected to have reinfarction and treated accordingly but had no symptomatic improvement and was planned for check angiography. However, based on dynamic electrocardiogram (ECG) changes, new echocardiographic findings aided laboratory parameters, he was diagnosed with acute pericarditis. He was treated with nonsteroidal anti-inflammatory drugs following which his pain resolved and ECG returned to baseline after 4 days. His follow-up echocardiography showed complete resolution of pericardial effusion. This case highlights the importance of keeping acute pericarditis as a differential diagnosis of chest pain in PCI patients. A high degree of suspicion is required, as most cases are easily missed to diagnose.